Can a channelized Hotelling observer assess image quality in acquired mammographic images of an anthropomorphic breast phantom including image processing?. Issue 2 (4th January 2019) - Balta, C.; Bouwman, R. W.; Sechopoulos, I.; Broeders, M. J. M.; Karssemeijer, N.; van Engen, R. E.; Veldkamp, W. J. H.
Abstract : Purpose: To study the feasibility of a channelized Hotelling observer (CHO) to predict human observer performance in detecting calcification‐like signals in mammography images of an anthropomorphic breast phantom, as part of a quality control (QC) framework. Methods: A prototype anthropomorphic breast phantom with inserted gold disks of 0.25 mm diameter was imaged with two different digital mammography x‐ray systems at four different dose levels. Regions of interest (ROIs) were extracted from the acquired processed and unprocessed images, signal‐present and signal‐absent. The ROIs were evaluated by a CHO using four different formulations of the difference of Gaussian (DoG) channel sets. Three human observers scored the ROIs in a two‐alternative forced‐choice experiment. We compared the human and the CHO performance on the simple task to detect calcification‐like disks in ROIs with and without postprocessing. The proportion of correct responses of the human reader (PCH ) and the CHO (PCCHO ) was calculated and the correlation between the two was analyzed using a mixed‐effect regression model. To address the signal location uncertainty, the impact of shifting the DoG channel sets in all directions up to two pixels was evaluated. Correlation results including the goodness of fit (r 2 ) of PCH and PCCHO for all different parameters were evaluated. Results: Subanalysis by system yielded strong correlations between PCH and PCCHO, with r 2 between PCH and PCCHO was found to be between 0.926 and 0.958 for the unshifted and between 0.759 and 0.938 for the shifted channel sets, respectively. However, the linear fit suggested a slight system dependence. PCCHO with shifted channel sets increased CHO performance but the correlation with humans was decreased. These correlations were not considerably affected by of the DoG channel set used. Conclusions: There is potential for the CHO to be used in QC for the evaluation of detectability of calcification‐like signals. The CHO can predict the PC of humans in images of calcification‐like signals of two different systems. However, a global model to be used for all systems requires further investigation.